Quicksilver - Koontz, Dean R. (Dean Ray), 1945- (Seattle : Thomas & Mercer, 2022)
"Quinn Quicksilver was born a mystery--abandoned at three days old on a desert highway in Arizona. Raised in an orphanage, never knowing his parents, Quinn had a happy if unexceptional life. Until the day of 'strange magnetism.' It compelled him to drive out to the middle of nowhere. It helped him find a coin worth a lot of money. And it practically saved his life when two government agents showed up in the diner in pursuit of him. Now Quinn is on the run from those agents and who knows what else, fleeing for his life." -- Book jacket
Keywords: Orphans -- Fiction; Extrasensory perception -- Fiction; Arizona -- Fiction; Thrillers (Fiction)